Effect of Ultrasonic Treatment on the Floatability of Chalcopyrite with Different Degrees of Oxidation - Zhiwei QI; Jin YAO; Wanzhong YIN; Wenju SUN (Kuangchan zonghe liyong)
Chalcopyrite is prone to surface oxidation during storage, which changes the surface properties and floatability of chalcopyrite, affects the subsequent flotation behavior and the adsorption of reagents on the surface of chalcopyrite. In view of the problem of poor flotation recovery of chalcopyrite due to oxidation, chalcopyrite was used as the research object, and chalcopyrite with different degrees of oxidation was prepared to investigate the effect of ultrasonic treatment on the surface properties and floatability of chalcopyrite with different degrees of oxidation. The results of single mineral flotation tests show that ultrasonic treatment in the xanthate system, the flotation recovery of chalcopyrite increased, the floatability improved, and the recovery rate of chalcopyrite by 23.26 percentage points. The effects of ultrasonic treatment on the wettability and surface roughness of oxidized chalcopyrite surfaces were analyzed using atomic force microscopy(AFM), scanning electron microscopy (SEM), and contact angle test.This provides a guiding idea for improving the flotation recovery of chalcopyrite.